Hubungan Tingkat Stres, Kecemasan, dan Depresi dengan Konstipasi Fungsional pada Mahasiswa Kedokteran - Z, Khafifah; Wilson, Wilson; Tejoyuwono, Agustina Arundina Triharja (Jurnal Penyakit Dalam Indonesia, 2024)
Introduction. Stress, anxiety, and depression are factors associated with functional constipation that affect students’ quality of life. Stress, anxiety, and depression are often experienced by first-year medical students, but studies assessing these three variables with functional constipation are still limited. Methods. This study used a cross-sectional analytical design. Study was carried out in July 2023 involving 88 first-year medical students from the Tanjungpura University Medical Study Program. Analysis of relationship tests was carried out using Kendall’s Tau-B tests. Results. Most students were in the normal category of stress, anxiety and depression levels, however 21 students were in mild to severe stress levels, 46 students were in mild to very severe anxiety levels, and 19 students were in mild to severe depression levels. Based on the assessment of functional constipation according to ROME IV, 20 students (22.73%) experienced functional constipation. There was a significant association between stress level (p=0.001), anxiety level (p=0.041), and depression (p=0.006) with functional constipation. Conclusion. There is a correlation between stress, anxiety and depression that influence functional constipation. Among first-year medical students at Tanjungpura University.